O23 Outcomes after non-operative management of perforated diverticular disease: a population based cohort study. (30th July 2021) - Adiamah, A; Ban, L; Otete, H; Crooks, C J; West, J; Humes, D J
Abstract: Introduction: The management of perforated diverticular disease has changed in the last 10 years with a move towards less surgical intervention. This population based cohort study aimed to define the risk of mortality and readmission following non-operative management of perforated diverticular disease (DD). Method: Patients diagnosed with perforated DD and managed without surgery were identified from the linked Clinical Practice Research Datalink and Hospital Episode Statistics data from 2000 to 2013. The outcomes were 1-year case-fatality, re-admissions and surgery at re-admission. Result: In total, 880 patients with perforated DD were managed without surgery, comprising of 523 females (59.4%). One year case-fatality was 33.2% (293/880). The majority of deaths occurred in the first 90 days following the index admission with a 90 day case-fatality of 28.8%. 90 day survival varied by age with 97.2% survival at 90 days in those under 65 years compared to 85.0% in those between 65–74 years and 51.5% in those over 75 years. Of 767 patients discharged from hospital, 250 (32.6%, 250/767) were re-admitted (47 elective(6.1%) and 203 emergency(26.5%)) during a median of 1.6 years of follow-up (iqr 0.1–3.9 years) with similar proportions in each age category. In the first year of follow-up only 5.1% of patients required surgery of whom 16/767 (2.1%) required elective and 23/767 (3.0%) emergency surgery. Conclusion: Conservative management of perforated diverticulitis in those under 65 years is feasible and safe. A third of patients are readmitted during follow-up, however, re-intervention rates following conservative management were low across all age categories. Take-home Message: In younger patients (<65yrs) conservative management of perforated diverticulitis is feasible and safe. A third of conservatively managed patients are readmitted during follow-up, however, need for surgery on readmission is rare.